Pathogenicity of different betanodavirus strains in Asian Seabass (Lates Calcarifer) under temperature fluctuation stress - Khairul Asri, Muhammad Safwan; Abdullah, Azila; Nawi, Mohd Firdaus; Mohd Idris, Shaharah; Ramly, Rimatulhana; Mansor, Nur Nazifah (2022)
Viral Nervous Necrosis (VNN) disease caused by betanodavirus infection is responsible for mass mortality in many marine cultured fish species. . Fish can acquire the disease by either horizontal or vertical transmission. Malaysian local betanodavirus strains were obtained from National Fish Health Research Centre, Penang and cultured in E-11 cell line. The isolates are Bawal Emas (BE), AVA and KL 22. Fifty-percent tissue culture infective dose (TCID50) calculations for all the isolates were conducted to evaluate the concentration of the virus. In this study, three hundred and sixty healthy seabass juveniles (5 ± 2g) with size two to three inches were obtained from Marine Fish Aquaculture Research Division, Terengganu was divided equally in eight tanks that represent four treatment groups with duplicates; Group 1 (AVA strains), Group 2 (BE strains), Group 3 (KL22 strains) and Group 4 (control). All the fish were observed daily for any clinical changes and mortality that occurred. Upon clinical signs appearing and mortality, the fish were slaughtered immediately and subjected to a polymerase chain reaction (PCR), cell culture and histology. The experiment was terminated after thirty days period. TCID 50 for all the tested strains are as follow; KL 22 = 104 TCID50/mL, BE = 107 TCID50/mL and AVA = 106 TCID50/mL. KL22 strain was found to have the highest TCID 50 followed by AVA and BE. Similarly, the highest mortality was also recorded in the group challenged with the KL22 strain which also has the highest TCLD 50. All the dead and sick fishes tested positive for PCR. However, the histology finding indicated no vacuolation found in the cell suggesting an acute infection has occurred.